Marginalisation of men in family planning texts: An analysis of training manuals. (June 2018) - Wilson, Amanda D; Fylan, Fiona; Gough, Brendan
Objective: Men's engagement in family planning has become part of the global health agenda; however, little is known about the training manuals health practitioners' use and how these manuals describe and explain men's roles within a family planning context. Design: To further understand engagement, this paper examines how training manuals written for health practitioners describe and define men's participation within family planning. Setting: The training manuals were written for UK health practitioners and covered men's contributions to family planning. Method: Discourse analysis was used to examine the three training manuals focused upon. Results: Three main discourses were identified: 'contraception is a woman's responsibility', 'men disengage with health practitioners' and 'men are biologically predisposed to avoid sexual responsibility'. Conclusion: Together, these three discourses function to marginalise men in family planning, constructing them as detached accessories that lack the ability to engage.